Understanding identity construction of an in-service pre-k teacher using discursive psychology - Zakaria, Faishal (Englisia Journal, 2023)
Experts have asserted that teacher identity is an integral part of classroom practices; studying teacher identity construction would allow us to understand the teachers’ learning process and teaching practices. It is then argued that identity is fluid and is never a stand-alone aspect. Further, many studies of the discursive construction of teacher identities have suggested teacher identity construction is highly contextual. However, little research has focused on how pre-K teachers serving low-income students and families construct their professional identities discursively. Grounded within the perspectives of Discursive Psychology,  this study is interested in how a US government-sponsored pre-K program teacher discursively constructs her identities. The findings further suggest the fluidity of identity and particularly posit that the teacher has constructed and claimed her collective and co-constructed identities, as well as discursively formed her identities as a person who values social capital, who is practical, who serves the needy students and families, who has power or resources, and who is a lifelong learner. The findings further implicate the need to consider teachers’ identities to understand their learning, growth, and classroom practices.